An On-Chip, Multichannel Droplet Sorter Using Standing Surface Acoustic Waves - Li, Sixing; Ding, Xiaoyun; Guo, Feng; Chen, Yuchao; Lapsley, Michael Ian; Lin, Sz-Chin Steven; Wang, Lin; McCoy, J. Philip; Cameron, Craig E; Huang, Tony Jun (Analytical chemistry (Washington), 2013)
The emerging field of droplet microfluidics requires effective on-chip handling and sorting of droplets. In this work, we demonstrate a microfluidic device that is capable of sorting picoliter water-in-oil droplets into multiple outputs using standing surface acoustic waves (SSAW). This device integrates a single-layer microfluidic channel with interdigital transducers (IDTs) to achieve on-chip droplet generation and sorting. Within the SSAW field, water-in-oil droplets experience an acoustic radiation force and are pushed toward the acoustic pressure node. As a result, by tuning the frequency of the SSAW excitation, the position of the pressure nodes can be changed and droplets can be sorted to different outlets at rates up to 222 droplets s–1. With its advantages in simplicity, controllability, versatility, noninvasiveness, and capability to be integrated with other on-chip components such as droplet manipulation and optical detection units, the technique presented here could be valuable for the development of droplet-based micro total analysis systems (μTAS).